Implementation of international human rights and labour standards in Lesotho and their impact on Basotho women - Makhera, Polello Sephora (Centre for Law and Society, 2021)
This study examines the position of women in Basotho society. It examines the position that women occupy in the society both in their traditional and contemporary roles. This is later contrasted to the developments made at the level of the state to effect changes to improve the situation. The data used in the study pertain to the period after 1986 up to 1996, except where it was possible to include more current. The international community has established norms intended to guide the members of the respective conventions and treaties in making of their domestic laws. These guidelines operate as an indication of the member country's intention to abide by the norms and not to deliberately flout the principles involved. Lesotho has through the years signed and ratified a number of these conventions. There has been quite a significant number of problems encountered in applying equality rights. Women in Lesotho as in the rest of the developing world are faced with discrimination on at least two levels, being female and being a member of the wrong race. The issue is whether they are also as humans, entitled to the benefit of universal human rights, or is it the exclusive preserve of men. It is the purpose of this study to examine the extent to which the international norms and human rights standards have impacted on the municipal law in Lesotho to grant equality rights to women. Finally, it is concluded that the Government of Lesotho has failed to achieve its obligations under the Conventions and international norms to which it has bound itself. Although legislation has been passed and applauded even at an international level, little progress can be made due to the half hearted attempts by the legislature to grant rights to women while not wanting to disturb the run of things and curtail the power that men have over them. This is likely not to be popular at some quarters especially with traditionalists. If however women are to be given equality in rights, the reforms have to be made.